Electron-capture modes with realistic nuclear structure calculations - Giannaka, P. G.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
Nuclear electron capture posses prominent position among other weak interaction processes occuring in explosive nucleosynthesis. In particular, this process plays important role in the core-colapse of massive stars by modifying the electron to baryon ratio Ye. From a nuclear theory point of view, such processes may be studied by using the same nuclear methods (e.g. the quasi-particle random phase approximation, QRPA), employed in the present work with these used for the one-body charge changing nuclear reactions (β-decay modes, charged-current electron-neutrino absorption by nuclei, etc). In this work we calculate e−-capture cross sections on 56Fe using two different approaches. At first, original cross section calculations are perfored by using the pn-QRPA method considering all the accessible transitions of the final nucleus 56Mn. Secondly, we evaluate the Gamow-Teller strength distributions and obtain the cross sections at the limit of zero-momentum transfer. The agreement between the two methods is very good.